National Program for Improving Access and Quality in Primary Care: trends in Brazilian theses and dissertations (Research, Society and Development, 2020)
This study aims to identify the tendencies of Brazilian theses and dissertations in the theme of the National Program for Improving Access and Quality of Primary Care. This is a systematic review of the literature, carried out in the databases of the Coordination Portal for the Improvement of Higher Level Personnel, in the Catalogs of the Center for Nursing Studies and Research and in the database of the Brazilian Institute of Information in Science and Technology. It was identified 185 studies, of which, 116 were evaluated, contemplating 22 theses and 92 dissertations. In the research universe, there is a constant increase on the subject from 2013, from 09 to 55 studies in 2016, comprising 23 Postgraduate Programs, concentrated in Regions of Brazil. The researches have presented evidences of the effectiveness of the program and the reflexes in the services of health in the Basic Attention, highlighting the potential of the PMAQ-AB in inducing to the improvements.